The Impact of the Psychological Capital on Job Performance: A Case Study on Faculty Members at Philadelphia University - Durrah, Omar; Al-Tobasi, Adnan; A'aqoulah, Ashraf; Ahmad, Moinuddin (International Review of Management and Marketing, 2016)
The present study aims to identify the perception of faculty members at Philadelphia University about the concept of psychological capital, measure the level of job performance, and determine the impact of the psychological capital on job performance. Using structured questionnaire, data was collected from (110) faculty members (assistant professor, associate professor, professor) from 8 faculties in Philadelphia University, Jordan. Multiple Regression analysis has been used to find the impact of psychological capital on job performance. Results show that the level of faculty members' awareness to the concept of psychological capital is high. In addition the Job performance was high in all dimensions. Moreover, it was found that hope dimension has a statistical effect on all dimensions of job performance. In addition, self-efficacy dimension affect statistically on behavioral performance dimension. Finally, the resilience dimension affect statistically on job performance dimension. However, the optimism dimension does not significantly affect any Job performance's dimensions. Keywords: Psychological Capital, Job Performance, Faculty Members, Philadelphia University, Jordan JEL Classifications: M10, M12